Appreciation to peer-reviewers 2018 - Pacheco-Romero, José (2018)
The Editorial Committee of the Peruvian Journal of Gynecology and Obstetrics (RPGO) thanks the renowned professionals, researchers and academics who contributed in a disinterested manner and promptly in the evaluations of the articles published in the RPGO Volume 64 issues 1, 2, 3 and 4 during the year 2018, through peer review.